Routing multiple cars in Singapore - Mao, Huiqi (2016)
Traffic congestion has become a universal metropolitan problem. As a result of traffic congestions, people are travelling with more time and higher cost. It brings down the overall productivity and traffic authorities also strive to solve this problem. A survey on traffic conditions during peak hours shows that the worst time to travel in Singapore is in the mornings (8-9am), and especially in areas near Clementi and Bukit Timah where it takes nearly 2.5 times longer to travel as compared to times when there is no traffic (1-5am). Worldwide, it is estimated that developed countries are spending $2,200 billion each year on traffic congestions. Traffic congestion is also causes individuals to suffer psychological distress and mood disorders, which could cause more impatience of drivers and more traffic accidents on the road, according to a study led by Susan Charles, a professor of psychology and social behavior. With routing services nowadays, cooperation between vehicles rarely exists. Each vehicle does its routing by itself based on the traffic conditions before the start of its journey. It hasno knowledge of where the other vehicles will be travelling to and which roads may get congested. It is very likely that large number of vehicles will choose to travel through the same road, for example the AYE from Clementi to the CBD area in Singapore. This is when a large number of vehicles will crowd to the same road and cause traffic congestions.